Methodology of the formation and implementation of state policy on the integration of the national healthcare system into the European medical space - Andrieiev, Ievhenii (Public Policy and Accounting, 2025)
A set of organizational and methodological provisions of the state policy for integrating the national healthcare system into the European medical space has been substantiated. The symptoms of the problem of integrating the national healthcare system into the European medical space have been identified; they characterize the current state of the national healthcare system, and their resolution is one of the key requirements of the European Union. The systemic problems of implementing the state policy on integrating the national healthcare system into the European medical space have been defined; these issues create obstacles to fulfilling EU requirements and, in some cases, have caused a crisis in Ukraine’s healthcare system. The initial principles of state policy on integrating the national healthcare system into the European medical space have been formulated. The key objects of state policy (human resources, infrastructure, and financial support) and the mechanisms for managing them (legal, organizational, and financial) have been determined.